MODERNIZATION EFFORTS OF THE OTTOMAN CALIPHATE DURING THE REIGN OF SULTAN ABDUL HAMID II - Danial, Danial; Adawiyah, Robi'atul; Muttaqin, Mohammad Izdiyan (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
This study examines the leadership of Sultan Abdul Hamid II in modernizing the Ottoman Caliphate during the late 19th and early 20th centuries. Amidst Western colonial pressures, internal fragmentation, and rising ethnic nationalism, he implemented modernization policies in education, infrastructure, and communication, while reinforcing religious symbolism through Pan-Islamism. The research adopts a qualitative approach using historical-critical and hermeneutic methods, utilizing primary sources such as official documents and speeches, alongside secondary sources like academic literature and archival materials. Early scholarship generally portrayed Abdul Hamid II as authoritarian, but more recent studies recognize his strategic role in developing modern education systems, financial institutions, and communication networks in response to global challenges. Findings indicate that despite his autocratic style, he initiated modernization projects such as the founding of technical and women’s schools, construction of railways—including the Hijaz Railway—and reforms in legal and military sectors. He also rejected Western diplomatic pressure on the Palestine issue and extended influence to non-Ottoman Muslim communities through religious diplomacy. However, his authoritarianism sparked opposition, particularly the Young Turk movement, which ultimately deposed him. This study concludes that Abdul Hamid II’s rule reflects an adaptive leadership model that combined authoritarianism, modernization, and religious legitimacy. It contributes to Islamic historiography and modern political studies by showing how religious symbolism and development were used as tools of diplomacy and social control. Limitations include a lack of microhistorical focus and insufficient exploration of Muslim perspectives beyond the imperial center, pointing to the need for further localized research.